Dealing with digital security risk during the Coronavirus (COVID-19) crisis (OECD Policy Responses to Coronavirus (COVID-19), 2020)
Digital security risk is increasing as malicious actors take advantage of the coronavirus (COVID-19) epidemic. Coronavirus-related scams and phishing campaigns are on the rise. There are also cases of ransomware and distributed denial of service (DDoS) attacks targeting hospitals. Individuals and businesses should exercise caution when they receive coronavirus-related communications, and use appropriate digital security "hygiene" measures (e.g. patching, use of strong and different passwords, regular backups, etc.). It is essential that governments raise awareness, monitor the threat landscape and publish easily accessible guidelines for digital security hygiene, in particular to vulnerable groups such as the elderly and small- and medium-sized enterprises (SMEs). Governments should also co-operate with all relevant stakeholders, including to provide assistance to operators of critical activities such as hospitals, as appropriate